On equilibrium equations of cylindrical shell with attached rigid body - Trotsenko, Y.V. (Нелінійні коливання, 2001)
The mechanical system consisting of a circular cylindrical shell and a rigid body attached to one of the shell ends is considered. In linear statements, the boundary-value problem on a stressedlydeformed state of this system under concentraited and distributed loads is formulated. The equations obtained can also be used for a study of free oscillations of the considered construction if one replaces the applied loads with forces of inertia and their moments.